Ù…ØÙ…Ø¯ Ø¹Ø¨Ø¯Ù‡ ÙˆØ§ØªØ¬Ø§Ù‡Ù‡ Ø§Ù„Ø£Ø¯Ø¨ÙŠ ÙÙŠ Ø§Ù„ØªÙØ³ÙŠØ± - Sihabuddin, Muhammad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2016)
This research strengthens the findings of the previous research which stated that Muhammad Abduh used literary paradigm in his Tafsir. Abduh, although he was known as a man of letters but there is a statement that it does not mean that Abduh’s Tafsir entirely stands on the methods and literary paradigm. Due to this reason the study is purposed. The findings of this research show that Abduh’s interpretation toward the Qur'an is not much different than what is done by the contemporary interpreters such as Amin Al-Khulli. The literary approach used by Abduh in interpreting the Qur'an it could be reviewed from linguistic description given upon words in the Qur'anic verses and the aspect of the history of the development of the meaning of those words. In addition, Abduh’s literary approach is also identical to rationalism tradition in the world of the Qur'anic exegesis scholarship. This caused Abduh to be accused as of the leftist Mu'tazilah. However, by using the inter-textual method, this research concludes that the allegation is not true.